2001
DOI: 10.1056/nejm200103013440902
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Low-Molecular-Weight Heparin on Thrombus Regression and Recurrent Thromboembolism in Patients with Deep-Vein Thrombosis

Abstract: In acute deep-vein thrombosis, reviparin regimens are more effective than unfractionated heparin in reducing the size of the thrombus. Reviparin is also more effective than unfractionated heparin for the prevention of recurrent thromboembolism and equally safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
1
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(124 citation statements)
references
References 31 publications
2
111
1
10
Order By: Relevance
“…14,23 All but 1 study 16 blinded outcome assessors. Only 2 studies blinded data analysts, 16,21 and only 2 studies blinded patients and caregivers.…”
Section: Methodologic Quality Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…14,23 All but 1 study 16 blinded outcome assessors. Only 2 studies blinded data analysts, 16,21 and only 2 studies blinded patients and caregivers.…”
Section: Methodologic Quality Of Included Studiesmentioning
confidence: 99%
“…Two articles did report the cancer subgroups data. 12,13 Three other articles [14][15][16] had follow-up publications reporting the cancer subgroup data. [17][18][19][20] We contacted the authors of the remaining 19 articles to request cancer subgroup data: One author provided us with the data 21 ; another author indicated that the data were not available anymore 22 ; we used the cancer subgroup data for 7 articles, 23-29 because they were reported in 2 published systematic reviews 5,8 ; and we were not able to obtain any outcome data for the remaining studies.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A range of options currently exist for thrombus resolution, including traditional anticoagulants, thrombolytic agents (such as streptokinase, urokinase, and recombinant tissue plasminogen activator), surgical embolectomy, and percutaneous catheter-directed treatment; [31][32][33] these approaches can be used alone or in combination in some cases.…”
Section: Treatment Approaches and Guidelines For Thrombus Resolutionmentioning
confidence: 99%
“…Unfortunately, a major disadvantage of LMWHs is that they can only be administered parenterally, due to a lack of absorption when administered orally [Breddin et al, 2001;Gran et al, 2001;Money and York, 2001]. The development of oral formulations for LMWH would have tremendous clinical importance as it would result not only in avoidance of the pain and discomfort associated with injections but would also reduce expenses associated with prolonged hospital stay and parenterals, thereby offering improved patient compliance.…”
Section: Introductionmentioning
confidence: 99%